Letter : International Brigade Association and Friends of Republican Spain - Campbell, J. S.
035-0022-001 THE NATIONAL UNION OF RAILWAYMEN Unity House, Euston Road, London, N.W.1 J.S. CAMPBELL General Secretary S.F. GREENE, J.P. FREDK. E. BELL, A.M. INST. T. Assistant General Secretaries Telegrams: "BEWARE, NORWEST" Telephone: EUSTON 4771 (5 LINES) Your Ref: International VT/AK/CW/208. In your reply refer to: GS/820. 20th November 1953. Sir Vincent Tewson, C.B.E., M.C., Trades Union Congress, Transport House, Smith Square, London, S.W.1. Dear Sir Vincent, International Brigade Association and Friends of Republican Spain. I desire to acknowledge receipt of and thank you for your letter of the 18th November, the contents of which have been noted. Yours sincerely, J. Campbell 292/946/35/22